2023
DOI: 10.1111/tra.12905
|View full text |Cite
|
Sign up to set email alerts
|

The role of extracellular vesicles in iron homeostasis and ferroptosis: Focus on musculoskeletal diseases

Abstract: Iron homeostasis is crucial for maintaining proper cellular function, and its disruption is considered one of the pathogenic mechanisms underlying musculoskeletal diseases. Under conditions of oxidative stress, the accumulation of cellular iron overload and lipid peroxidation can lead to ferroptosis. Extracellular vesicles (EVs), serving as mediators in the cell‐to‐cell communication, play an important role in regulating the outcome of cell ferroptosis. Growing evidence has proven that EV biogenesis and secret… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 159 publications
0
1
0
Order By: Relevance
“…Brent R. Stockwell identified metabolism, ROS, and iron biology as pivotal regulators of ferroptosis [8] . Moreover, a plethora of studies have also demonstrated that intracellular iron-loading status is necessary for intracellular ferroptosis [ 9 , 10 ]. Furthermore, it has been discovered that intracellular iron overload, which is mediated by hepcidin and ferroportin (FPN1), is the key link to the occurrence of ferroptosis [ 8 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Brent R. Stockwell identified metabolism, ROS, and iron biology as pivotal regulators of ferroptosis [8] . Moreover, a plethora of studies have also demonstrated that intracellular iron-loading status is necessary for intracellular ferroptosis [ 9 , 10 ]. Furthermore, it has been discovered that intracellular iron overload, which is mediated by hepcidin and ferroportin (FPN1), is the key link to the occurrence of ferroptosis [ 8 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Apoptosis is a form of programmed cell death mediated by extrinsic or intrinsic pathways that allow for the removal of damaged cells [10]. The biogenesis and release of EVs have been shown to be associated with the export of cellular iron [11]. Wu et al identified multiple ferroptosis-related genes in syncytiotrophoblast-derived EVs [12].…”
Section: Introductionmentioning
confidence: 99%